A Critical Study of Women Portrayed in Shakespearian Play: Exploring Shakespeare's Complex Depiction of Women (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The portrayal of women by Shakespeare and its ways of understanding performing her leading leads have become subjects of discussion to concern. The heroines of Shakespeare encompass a number of forms and characteristics. Shakespeare's women display tremendous intellect, vitality a clear sense of self-sufficiency in his gallery of female characters. Some commentators have found Shakespeare to be a female champion innovator who has sharply left his contemporaries earlier dramaticians with stereotypical traits, which are typical to women. In comparison, other critics note that even Shakespeare 's best-pictured women have characters with derogatory characteristics. In this essay, Shakespeare's portrayal of women in his tragedies showing his feelings about women their role in society was attempted.